2016
DOI: 10.1007/s11665-016-2089-1
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Light MMCs Modified with Cordierite Synthesized from Fly Ash

Abstract: This paper presents novel opportunities for management of fly ash by synthesizing the material into cordierite ceramics and using it as a reinforcing phase for light metal alloys. Metal matrix composites (based on magnesium alloy and aluminum alloy) were produced by squeeze casting. The magnesium matrix composites with a suitably selected reinforcing phase content (2 wt.%) exhibited much better strength properties than the unmodified alloy (AM60). It was also demonstrated that the wettability (or the lack ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is a characteristic component of the microstructure of the AZ91 (MgAl9Zn1) alloy casting, and its morphology depends on both the alloy composition (including Al concentration) and the solidification rate. The lamellar morphology of the Mg 17 Al 12 phase precipitates with a clear growth anisotropy may be caused by the directional correlation of crystallographic orientations with the α phase [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a characteristic component of the microstructure of the AZ91 (MgAl9Zn1) alloy casting, and its morphology depends on both the alloy composition (including Al concentration) and the solidification rate. The lamellar morphology of the Mg 17 Al 12 phase precipitates with a clear growth anisotropy may be caused by the directional correlation of crystallographic orientations with the α phase [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…They have concluded that cordierite is started to form at 1200°C and the pure phase is obtained at 1300°C with a small amount of spinel. Dong et al (2006) [159], Liu et al (2015) [160] and Długosz et al (2016) [161] have also used FA to fabricate the cordierite ceramics. Zhu et al (2012) [162] have prepared cordierite by solid-state reactions with three different types of raw materials, i.e., waste kaolin mine tailing as the source of SiO 2 and Al 2 O 3 , waste serpentine mine tailing as the source of SiO 2 and MgO, and alumina powder.…”
Section: Cordieritementioning
confidence: 99%